1997
DOI: 10.1063/1.365783
|View full text |Cite
|
Sign up to set email alerts
|

Space charge effects on the current-voltage characteristics of gated field emitter arrays

Abstract: Interplay of current crowding and current self-quenching effects in planar cold cathodes Space-charge effects and current self-quenching in a metal/CdS/LaS cold cathode Effects of space charge on the current-voltage characteristics of field emitter arrays AIP Conf.Microfabricated field emitter arrays ͑FEAs͒ can provide the very high electron current densities required for rf amplifier applications, typically on the order of 100 A/cm 2 . Determining the dependence of emission current on gate voltage is importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 19 publications
(15 reference statements)
2
26
0
Order By: Relevance
“…The work function typically used for Mo is 4.3-4.4 eV. 79 Performance degradation rates were predicted assuming three different work function values and the same E^ value of 39 eV. The results showed that performance degradation rates predicted using each <| > w value were consistent with experimental results when an E^ value of 39 eV was used.…”
Section: Mo Sri International Cathodesupporting
confidence: 71%
“…The work function typically used for Mo is 4.3-4.4 eV. 79 Performance degradation rates were predicted assuming three different work function values and the same E^ value of 39 eV. The results showed that performance degradation rates predicted using each <| > w value were consistent with experimental results when an E^ value of 39 eV was used.…”
Section: Mo Sri International Cathodesupporting
confidence: 71%
“…In experiments, the gate is not a ring of charge, and a sheet of charge representing the remainder of the gate [113] must be added. The potential on axis becomes…”
Section: Gated Geometries and Triodesmentioning
confidence: 99%
“…If higher terms were retained, A FN and B FN would no longer be constant but would depend on x = 1/V and therefore, become local intercept and slope parameters (see discussion in Ref. [113]). In terms of data, x 0 represents the midpoint of 1/V , and δ governs the range over which 1/V varies.…”
mentioning
confidence: 99%
“…Nevertheless, there have been several theoretical efforts [11][12][13][14][15][16]: in particular, the treatment of the 1D field emission / space charge problem (Ref. [17] and references therein), the usage of Particle-in-Cell codes to treat field emission (Ref.…”
Section: Introductionmentioning
confidence: 99%